Comparison of transcutaneous electrical nerve stimulation and lidocaine on episiotomy complication in primiparous women: A randomized clinical trial - Maryam Rezaeyan; Mehrnaz Geranmayeh; Ashraf Direkvand-Moghadam (Wolters Kluwer Medknow Publications, 2017)
Introduction: Transcutaneous electrical nerve stimulation (TENS) through the skin is a nonpharmacological method of pain relief. The present study aimed to compare TENS and lidocaine on episiotomy complication in primiparous women. Material and Methods: In a randomized, controlled clinical trial, 80 participants were included from March to July 2011 at the antenatal clinic and postdelivery ward in the Social Security Organization Hospital, Khorramabad, Lorestan, Iran. Data were collected using a demographic questionnaire, visual analog scale and redness, edema, ecchymosis, discharge, and approximation scales. The participants were randomized into two groups with equal number of participants. All participants received 5 cc of local infiltration of 1% lidocaine before episiotomy, and TENS electrodes were placed on He Gu and Shenmen points during the crowning of fetal head. The TENS group received TENS with 100; 250 μs, the output range of 15-20 mm amplifier from crowning of first stage of labor to the end of the episiotomy repairing. The lidocaine group received 10 cc of local infiltration of 1% lidocaine before episiotomy repair while did not receive TENS electrodes. The pain intensity during and after episiotomy repair was recorded. Results: TENS and lidocaine have similar effects on pain relief at the episiotomy cutting, the start of the episiotomy repair, and at end of the episiotomy repair; however, the pain relief of both the interventions was different during the episiotomy repair. The effect of TENS in reducing edema was statistically significant (P = 0.001). Conclusions: TENS and lidocaine are effective for the episiotomy complications during and after episiotomy repair.